# Solve for h 1/p+1/r=1/h

1p+1r=1h
Rewrite the equation as 1h=1p+1r.
1h=1p+1r
Find the LCD of the terms in the equation.
Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.
h,p,r
Since h,p,r contain both numbers and variables, there are two steps to find the LCM. Find LCM for the numeric part 1,1,1 then find LCM for the variable part h1,p1,r1.
The LCM is the smallest positive number that all of the numbers divide into evenly.
1. List the prime factors of each number.
2. Multiply each factor the greatest number of times it occurs in either number.
The number 1 is not a prime number because it only has one positive factor, which is itself.
Not prime
The LCM of 1,1,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.
1
The factor for h1 is h itself.
h1=h
h occurs 1 time.
The factor for p1 is p itself.
p1=p
p occurs 1 time.
The factor for r1 is r itself.
r1=r
r occurs 1 time.
The LCM of h1,p1,r1 is the result of multiplying all prime factors the greatest number of times they occur in either term.
h⋅p⋅r
Multiply hp by r.
hpr
hpr
Multiply each term by hpr and simplify.
Multiply each term in 1h=1p+1r by hpr in order to remove all the denominators from the equation.
1h⋅(hpr)=1p⋅(hpr)+1r⋅(hpr)
Cancel the common factor of h.
Factor h out of hpr.
1h⋅(h(pr))=1p⋅(hpr)+1r⋅(hpr)
Cancel the common factor.
1h⋅(h(pr))=1p⋅(hpr)+1r⋅(hpr)
Rewrite the expression.
pr=1p⋅(hpr)+1r⋅(hpr)
pr=1p⋅(hpr)+1r⋅(hpr)
Simplify each term.
Cancel the common factor of p.
Factor p out of hpr.
pr=1p⋅(p(hr))+1r⋅(hpr)
Cancel the common factor.
pr=1p⋅(p(hr))+1r⋅(hpr)
Rewrite the expression.
pr=hr+1r⋅(hpr)
pr=hr+1r⋅(hpr)
Cancel the common factor of r.
Factor r out of hpr.
pr=hr+1r⋅(r(hp))
Cancel the common factor.
pr=hr+1r⋅(r(hp))
Rewrite the expression.
pr=hr+hp
pr=hr+hp
pr=hr+hp
pr=hr+hp
Solve the equation.
Rewrite the equation as hr+hp=pr.
hr+hp=pr
Factor h out of hr+hp.
Factor h out of hr.
h(r)+hp=pr
Factor h out of hp.
h(r)+h(p)=pr
Factor h out of h(r)+h(p).
h(r+p)=pr
h(r+p)=pr
Divide each term by r+p and simplify.
Divide each term in h(r+p)=pr by r+p.
h(r+p)r+p=prr+p
Cancel the common factor of r+p.
Cancel the common factor.
h(r+p)r+p=prr+p
Divide h by 1.
h=prr+p
h=prr+p
h=prr+p
h=prr+p
Solve for h 1/p+1/r=1/h

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top